Mendelian randomisation analysis of the effect of educational attainment and cognitive ability on smoking behaviour - Eleanor Sanderson (Nature Portfolio, 2019)
Higher educational attainment is positively associated with a number of health outcomes. Here, Sanderson et al. use multivariable Mendelian randomisation analysis to test whether the association of educational attainment with smoking behaviour is direct or indirectly mediated via general cognitive ability.